Association between Helicobacter pylori Infection and Graves’ Disease: A Meta-Analysis - Guntur Darmawan; Marcellus Simadibrata; Indah Suci Widyahening (The Indonesian Society for Digestive Endoscopy, 2017)
Background: Helicobacter pylori (H. pylori) infection is proposed to be related with autoimmune diseases, such as Graves’ disease. This study aimed to assess the association between H. pylori infection and Graves’ disease.Method: A systematic literature review was conducted using Pubmed and Cochrane library. The quality of enrolled studies was assessed by the Critical Appraisal Skills Program Oxford. A fixed-effect model approach was used if there was no heterogeneity; otherwise, a random-effect model was used. Heterogeneity was assessed using I2. Publication bias was assessed by funnel plot. All data were analyzed using REVIEW MANAGER 5.3.Results: Six studies from Europe and Asia involving 983 patients were included. Overall H. pylori infection was significantly associated with Graves’ disease (OR = 2.7; 95% CI: 1.47-4.99; p 0.001). In subgroup analysis of 3 studies using non-serological diagnostic method, the prevalence rate of H. pylori infection was higher in Graves’ disease group (78.26% vs. 42.42%) with significant relationship (OR = 4.93; 95% CI: 3.16-7.69; p 0.00001; I2 = 0%). The Cytotoxin associated gene A (CagA) antibody prevalence was significantly higher in Graves’ disease group (46.57% vs. 20.29%; OR = 4.41; 95% CI: 2.65-7.33; p 0.00001; I2 = 56%). No publication bias was observed.Conclusion: Our study showed association between H. pylori infection and Graves’ disease. It might suggest the need of H. pylori examination in Graves’ disease patients and the impact of H. pylori eradication in the treatment of Graves’ disease.